2018
DOI: 10.18632/oncotarget.25208
|View full text |Cite
|
Sign up to set email alerts
|

Oncodriver inhibition and CD4+ Th1 cytokines cooperate through Stat1 activation to induce tumor senescence and apoptosis in HER2+ and triple negative breast cancer: implications for combining immune and targeted therapies

Abstract: In patients with HER2-expressing breast cancer many develop resistance to HER2 targeted therapies. We show that high and intermediate HER2-expressing cancer cell lines are driven toward apoptosis and tumor senescence when treated with either CD4+ Th1 cells, or Th1 cytokines TNF-α and IFN-γ, in a dose dependent manner. Depletion of HER2 activity by either siRNA or trastuzumab and pertuzumab, and subsequent treatment with either anti-HER2 Th1 cells or TNF-α and IFN-γ resulted in synergistic increased tumor senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 91 publications
2
26
0
Order By: Relevance
“…Interestingly, post-vaccine recruitment of CD4 pos T cells into peritumoral areas strongly predominate over CD8 pos T cells, suggesting an effector mechanism dependent at least in part on Th cells. Consistent with this notion, we and others have found that paired Th1 cytokines IFN-γ and TNF-α induced senescence and/or apoptosis in vitro for a variety of cancer cell lines (both human and murine) [5][6][7]. We also showed that in many cases these cytokines could drive down the expression of HER family members on the surface of breast cancer cells [6].…”
Section: Introductionsupporting
confidence: 86%
“…Interestingly, post-vaccine recruitment of CD4 pos T cells into peritumoral areas strongly predominate over CD8 pos T cells, suggesting an effector mechanism dependent at least in part on Th cells. Consistent with this notion, we and others have found that paired Th1 cytokines IFN-γ and TNF-α induced senescence and/or apoptosis in vitro for a variety of cancer cell lines (both human and murine) [5][6][7]. We also showed that in many cases these cytokines could drive down the expression of HER family members on the surface of breast cancer cells [6].…”
Section: Introductionsupporting
confidence: 86%
“…TP53 mutant cells are more sensitive to DNA damage (Brown and Wouters, 1999; Bunz et al, 1999), but cells that survive can undergo p53-independent senescence in culture (Chang et al, 1999b). Indeed, we found that in two TP53 mutant breast cancer cell lines shown to become senescent after chemotherapy, BT474 (Rosemblit et al, 2018) and T47D (Rastogi et al, 2006), cells that survived chemotherapy could engulf neighboring NT cells (Fig. 3, B and C).…”
Section: Resultsmentioning
confidence: 94%
“…Although TNF-α can be found at BC tissue level, to date it is unknown whether the TNF-α surrounding the tumor is produced and released by cancer cells as an evasion strategy from the host immune response or whether it is secreted by cells of the immune system that infiltrate the tumor tissue. Recent evidences reported that HER2-overexpressing BC cells are susceptible to apoptosis induced in vitro by T helper 1 cytokines as TNF-α [46,47]. Through a complex regulatory network, after its receptor activation, TNF-α has been found to induce apoptosis or necrosis but also an opposite effect inducing cell growth, invasion or propagation of cancer cells [48,49].…”
Section: Discussionmentioning
confidence: 99%